Y- GENERATION MENJADI IMAM?: PENDIDIKAN CALON IMAM KATOLIK DI INDONESIA DALAM TERANG DEKRIT OPTATAM TOTIUS - Simbolon, Subandri (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2018)
Formation of priest candidates is a very important element in the Catholic Church. The formandi (seminarians) are formed in a holistic manner to achieve the unity of faith, personal and intellectual. Formation system is prepared from Midle Seminary to High Seminary. However, changing times is inevitable. It also affects the changes in each individual, especially the seminarians. In Indonsia, the seminarians in this era can be included in Generation Y (Gen Y). Gen Y certainly bring problems and challenges in the formation process. This article aims to analyze how the Catholic Church, especially through Decret Optatam Totius, respons to issue of Gen-Y presence in Priest candidates formation. By basing the writing on ethnographic interviews, and analysis of any related text, the author described this in a systematic discussion paper. The first section, the introduction explains Y-Generation issue as a challenge that must be faced. In the second part, explains the form of education the Catholic priest candidates. Finally, elaborate the challenges, expectations, the outhor try to give proposals into the Priest candidates formation process.Key words: Y-Generation, Catholic priest candidate, leadership, responsible.